Level of Knowledge, Handling Sports Injuries, using the RICE Method, at the Banjar Regency Sports Teachers Association - Ariansyah; Aryadi Rachman; M. Mulhim (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The research aims to determine and describe the level of knowledge of handling sports injuries using the RICE Method at the Banjar Regency Sports Teachers Association. The method used in this research is a descriptive method, namely describing or illustrating events that are currently occurring using non-experimental methods using survey techniques (Hasan Syahrizal, 2023). An overview of the level of knowledge of handling sports injuries using the RICE method at the Banjar Regency Sports Teachers Association was 158 respondents, with details of a very high classification of 44 people with a percentage of 28%, a high classification of 105 people. people with a percentage of 66%, 9 people in the medium classification with a percentage of 6%, and 0% in the low and very low classification. The high results were because previously the Banjar Regency Sports Teachers Association had taken training in handling injuries and first aid in accidents. The Banjar Regency Sports Teachers Association, apart from being physical education, sports and health teachers, also has other professions such as coaches, referees, personal trainers, athletes, sports instructors and therapists. This research provides information to the Banjar Regency sports teacher association about handling Sports Injuries so that they can understand and apply injury treatment and prevent further injuries using the RICE Method. In addition, this research activity can improve and expand understanding of the treatment of sports injuries, as well as contribute to scientific studies in the field of sports science.